Bioinspired superwetting surfaces for biosensing. Issue 1 (13th August 2020) - Zhu, Hai; Huang, Yu; Lou, Xiaoding; Xia, Fan
Abstract: Inspired by nature, scientists and researchers have studied the wetting behaviors on various creatures and mimicked their structures to fabricate diverse functional superwetting materials. As one kind of emerging application, the bioinspired superwettable surfaces used for biosensing have been aroused wide interests. In this review, we summarized the recent developments of bioinspired superwettable surfaces in the field of biosensing. In the first part, superwettable creatures in nature, namely, superhydrophobic self‐cleaning lotus leaf, high‐adhesion superhydrophobic rose petal, amphiphobic springtail, patterned wetting desert beetles, slippery pitcher plant, were introduced. In sequence, we successively described the special wetting models of superhydrophobicity, superamphiphobicity, responsive wettability, patterned wettability, and slipperiness. Then, biosensing applications based on the respective patterned wettable, superhydrophobic, responsive wettable, and slippery substrates that were combined with the common detection approaches (colorimetry, fluorescence, surface‐enhanced Raman scattering (SERS), electrochemistry) were shown in detailed. At last, an insight of remaining challenges and future development for bioinspired superwetting materials applied in biosensing was provided. Abstract : Inspired by nature, the developments of bioinspired superwetting surfaces applied in biosensing are showed.